Inocuidad de las almendras y nibs, como residuo de la poscosecha del cacao (Theobroma cacao L.) para la elaboración de Granola en la Asociación “La Cruz”. - Barzola Carcamo, Luigin Alberto (2016)
The aim was used five formulations of a product called granola, elaborated with almond mixture and cocoa nibs National Association "La Cruz" in the Municipality of Mocache were evaluated. Was used a design completely randomized with five treatments and four repetitions with Tukey's test at 5% probability, with the following treatments: control (0% almonds and cocoa nibs National); T1: (10% almond and Cocoa nibs National); T2: (15% almond and Cocoa nibs National); T3: (20% almond and Cocoa nibs National) and T4 (25% almond and Cocoa nibs National). the proximal composition of the granola was analyzed, the physico-chemical properties (hygroscopic moisture, dry matter, ash, organic matter, pH, Protein, treatable acidity and fat), the (smell, color, taste, texture and acceptability) sensory properties and a microbiological analysis to better treatment according to the sensory analysis (aerobic mesophilic bacteria, molds and yeasts, Bacillus cereus and total coliforms). It was determined that the addition of almonds and nibs National cocoa not influence the amount of organic matter, ash and fiber in granola, while moisture, dry matter, pH, titratable acidity, protein and fat are closely, influenced by adding almonds and cocoa nibs, it ie that as increases in granola, levels almonds and cocoa nibs presents a decrease in dry matter, organic matter and moisture, acidity, protein and increases Witness against fat. In sensory analysis, the best treatment is T1 (10% almonds and nibs National Cacao), which stood on the acceptability, also in the microbiological analysis did not show total coliforms or molds and yeasts unlike aerobic mesophilic bacteria and Bacillus cereus where a small percentage was demonstrated, indicating that the granola is within permissible limits stipulated by the NTE INEN 2595-2011 standard.